Core set of unfavorable events of proximal humerus fracture treatment defined by an international Delphi consensus process - Laurent Audigé (BMC, 2021)
Abstract Background Proximal humerus fracture (PHF) complications, whether following surgery or nonoperative management, require standardization of definitions and documentation for consistent reporting. We aimed to define an international consensus core event set (CES) of clinically-relevant unfavorable events of PHF to be documented in clinical routine practice and research. Methods A Delphi exercise was implemented with an international panel of experienced shoulder trauma surgeons selected by survey invitation of AO Trauma members. An organized list of PHF events after nonoperative or operative management was developed and reviewed by panel members using on-line surveys. The proposed core set was revised regarding event groups along with definitions, specifications and timing of occurrence. Consensus was reached with at least a two-third agreement. Results The PHF consensus panel was composed of 231 clinicians worldwide who responded to at least one of two completed surveys. There was 93% final agreement about three intraoperative local event groups (device, osteochondral, soft tissue). Postoperative or nonoperative event terms and definitions organized into eight groups (device, osteochondral, shoulder instability, fracture-related infection, peripheral neurological, vascular, superficial soft tissue, deep soft tissue) were approved with 96 to 98% agreement. The time period for documentation ranged from 30 days to 24 months after PHF treatment depending on the event group and specification. The resulting consensus was presented on a paper-based PHF CES documentation form. Conclusions International consensus was achieved on a core set of local unfavorable events of PHF to foster standardization of complication reporting in clinical research and register documentation. Trial registration Not applicable.